Comunicación asertiva en redes sociales y la retroalimentación obtenida por la audiencia - Chipre Terán, Willy Elihú (2023)
The research project entitled: "Analysis of the assertive communication of the decentralized autonomous government of the Lomas de Sargentillo canton in the informative content, through its official Facebook page and feedback in young people from 18 to 22 years old" is investigated with the purpose of knowing the strategies of the cantonal government when communicating to its audience. In Lomas de Sargentillo, citizens are informed through digital platforms, however, it is not known if this content is broadcast assertively and what is the feedback obtained by the audience. For this study, a quantitative and qualitative approach was applied to study the behavior of young people on this social phenomenon. After analysis, a proposal is made to implement it on the cantonal government page.